Vibration Analysis by the Wigner-Ville Transformation Method - Jaroslav Smutny; Viktor Nohal; Daniela Vukusicova; Herbert Seelmann (Communications - Scientific letters of the University of Zilina, 2018)
This paper deals with description and application of the Wigner-Ville transformation for vibration analysis. This transformation belongs to the group of non-linear time-frequency processes. Thanks to its properties, it may be successfully used in the area of non-stationary and transitional signals describing various natural processes. The use in the field of the railway constructions testing represents a quite an interesting application area of the transformation. This paper contains mathematical analysis of the transformation, a case study and practical experience obtained and recommendations for its practical use.